I registro Brasileiro de insuficiência Cardíaca – Aspectos clínicos, qualidade assistencial e desfechos hospitalares - de Albuquerque, Denilson Campos; Neto, João David de Souza; Bacal, Fernando; Rohde, Luiz Eduardo Paim; Bernardez-Pereira, Sabrina; Berwanger, Otavio; Almeida, Dirceu Rodrigues; Reis, Helder José Lima; Nogueira, Paulo Roberto; Pavanello, Ricardo; Danzmann, Luiz Claudio; Santos, Elizabete Silva Dos; et al. (Sociedade Brasileira de Cardiologia, 2015)
Heart failure (HF) is one of the leading causes of hospitalization in adults in Brazil. However, most of the available data is limited to unicenter registries. The BREATHE registry is the first to include a large sample of hospitalized patients with decompensated HF from different regions in Brazil. Objective: Describe the clinical characteristics, treatment and prognosis of hospitalized patients admitted with acute HF. Methods: Observational registry study with longitudinal follow-up. The eligibility criteria included patients older than 18 years with a definitive diagnosis of HF, admitted to public or private hospitals. Assessed outcomes included the causes of decompensation, use of medications, care quality indicators, hemodynamic profile and intrahospital events. Results: A total of 1,263 patients (64 ± 16 years, 60% women) were included from 51 centers from different regions in Brazil. The most common comorbidities were hypertension (70.8%), dyslipidemia (36.7%) and diabetes (34%). Around 40% of the patients had normal left ventricular systolic function and most were admitted with a wet-warm clinical-hemodynamic profile. Vasodilators and intravenous inotropes were used in less than 15% of the studied cohort. Care quality indicators based on hospital discharge recommendations were reached in less than 65% of the patients. Intrahospital mortality affected 12.6% of all patients included. Conclusion: The BREATHE study demonstrated the high intrahospital mortality of patients admitted with acute HF in Brazil, in addition to the low rate of prescription of drugs based on evidence.
I Brazilian registry of heart failure - Clinical aspects, care quality and hospitalization outcomes
Keywords: Epidemiology; Heart failure/mortality; Hospitalization; Inappropriate prescribing